Pengaruh Kualitas Makanan Terhadap Kepuasan Konsumen di Royal Tulip Gunung Geulis Resort & Golf Hotel Bogor - Julia R. Skawanti; Riani Ishak; Salsabila Alhadar (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Food is one of the main products offered in the tourism industry, especially in hotels. Intense competition among similar businesses requires the Royal Tulip Gunung Geulis Resort & Golf Bogor to continuously innovate and maintain service quality. Customer complaints regarding food quality not meeting expectations serve as the background for this study. This research adopts a quantitative approach with the aim of presenting data in a structured, comprehensive, valid, and accountable manner. Data analysis was conducted using descriptive quantitative techniques. A total of 100 respondents, consisting of customers or guests who had consumed food at the Royal Tulip Gunung Geulis Resort & Golf Bogor during 2022, were selected as the sample using Non-Probability Sampling and incidental sampling techniques. Data were collected through a questionnaire and processed using regression analysis with SPSS 28 software. The results of this study indicate a significant influence of food quality on customer satisfaction at the hotel. This is evidenced by a t-value greater than the critical t-value (11.356 > 1.984) and a significance value smaller than 0.05 (0.01 < 0.05). The relationship is strong, with a correlation coefficient of 0.754, where food quality contributes 56.8% to customer satisfaction, while the remaining 43.2% is influenced by other variables not examined in this study